2021
DOI: 10.1007/s12633-021-01405-9
|View full text |Cite
|
Sign up to set email alerts
|

Design of Cold Plasma Based Ternary Photonic Crystal for Microwave Applications

Abstract: In this paper, we propose a Silicon/Plasma/Air ternary 1D photonic crystal, whose transmission and reflection properties have been studied. We draw the transmittance and reflectance versus frequency spectra in microwave region (GHz) for RHP Plasma based ternary PC by changing the angle of incidence for a fixed value of unit cells, magnetic field, layer thickness, collision frequency, and electron density. It is observed that with increase in angle of incidence, there is increase in photonic bandgap obtained in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…One commonly used method for examining the transmission properties of photonic crystals is the transfer-matrix method (TMM) [34][35][36]39]. The TMM simulation was performed using a homemade code in MATLAB software.…”
Section: Theoretical Model and Numerical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One commonly used method for examining the transmission properties of photonic crystals is the transfer-matrix method (TMM) [34][35][36]39]. The TMM simulation was performed using a homemade code in MATLAB software.…”
Section: Theoretical Model and Numerical Methodsmentioning
confidence: 99%
“…By controlling its structure and periodicity, precise control and modulation of optical waves can be achieved. In optical communication systems, multi-channel filters and wavelength division multiplexers are widely used [16,[23][24][25][26][27][28][29][30][31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…Using TMM, the characteristic matrix for a unit cell is expressed as [ 1,23 ] M()dbadbreak=j=13[]cosτjbadbreak−iξjsin0.16emτjiξjsinτjcos0.16emτj$$\begin{equation}M\left( d \right) = \mathop \prod \limits_{j = 1}^3 \left[ { \def\eqcellsep{&}\begin{array}{@{}*{2}{c}@{}} {{\rm{cos}}\,{\tau _j}}&\quad { - \frac{i}{{{\xi _j}}}{\rm{sin}}\,{\tau _j}}\\[6pt] {\mathop { - \,i\,\xi }\nolimits_{j\,} {\rm{sin}}\,{\tau _j}}&\quad {{\rm{cos}}\,{\tau _j}} \end{array} } \right]\end{equation}$$where τj=(ω/c1.0ptnjdj)cosθj${\tau _j} = ( {\omega /c{\kern 1pt} {n_j}{d_j}} ){\rm{cos}}{\theta _j}$, θ j is the ray angle inside layer‐ j ( j = A, B, and C layers). For the transverse electric (TE) polarization, we express introduce a parameter as, ξj=εj/μjcos0.16emθj${\xi _j} = \sqrt {{\varepsilon _j}/{\mu _j}} {\rm{cos}}\,{\theta _j}$; and we defineξj=μj/εjcosθj${\xi _j} = \sqrt {{\mu _j}/{\varepsilon _j}} {\rm{cos}}{\theta _j}$, for TM polarization; where cosθj=1false(n020.16emsin2θ0/nj2false)${\rm{cos}}{\theta _j} = \sqrt {1 - (\mathop n\nolimits_0^2 \mathop {\,{\rm{sin}}}\nolimits^2 \mathop \theta \nolimits_0 /\mathop n\nolimits_j^2 )} $, is the incident angle in air whose refractive index n 0 = 1.…”
Section: Theoretical Modelmentioning
confidence: 99%
“…[15] The optical properties, including band structure and group velocity characteristics, inside a 1DPC containing negative index materials, have been analyzed using translational matrix method (TMM) by Pandey et al [16][17][18][19][20][21] Among ternary PCs, the photonic bandgap (PBG) in a ternary metal/dielectric PC was theoretically investigated at the normal incidence. [22] Kumar et al [23] have suggested multichannel filter application of a magnetized-cold-plasma based 1D ternary PC and analyzed its band tunability depending on the various parameters. Since 2019, several research articles have been published on metamaterial-based ternary PCs and with their applications in different frequency regions, including giga-hertz (GHz), tera-hertz (THz) and near-infrared (IR), and low frequency waves.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation